Synergistic Collaboration of Pharmacists and Nurses in Enhancing Patient Care - Abida (Asian Journal of Pharmaceutics (AJP), 2024)
Collaboration between pharmacists and nurses is widely seen as an important synergistic collaboration in enhancing patient care by addressing issues such as drug mistakes, growing healthcare expenditures, and complex illness management. Their combined expertise enhances patient care by optimizing drug therapy, improving patient education, and reducing preventable medication-related issues. This article reflects the synergistic collaboration of pharmacists and nurses in enhancing patient care. A literature analysis was done to investigate research on multidisciplinary interaction between pharmacists and nurses in diverse healthcare settings, with an emphasis on their roles in drug management, patient education, and therapy optimization to reduce any avoidable interactions. Collaboration dramatically lowers medication mistakes, increases patient adherence, and improves overall clinical results, including chronic disease management. Despite the benefits, communication gaps and ambiguous responsibilities hinder successful synergistic collaboration. Addressing these hurdles through improved training and integration of certain healthcare systems software for better collaboration is critical to maximize the advantages of this collaborative effort. Pharmacist-nurse collaboration improves patient care and safety, and overcoming current obstacles can lead to more efficient, patient-centered healthcare systems. Despite the great perks of collaboration, there are certain obstacles to smooth collaborations. These obstacles can be addressed by providing proper training and integration of AI and other technical software for a smooth collaboration. With the partnership between pharmacists and nurses, much scope will be realized to improve patient-centered care. The removal of present obstacles and incitement of closer collaboration will make it possible for healthcare systems to improve clinical results, lower prescription errors, and guarantee more effective and patient-focused care delivery.